Diseño e implementación de un sistema de gestión de información de equipos biomédicos de la óptica Dr. Pava - Diaz Torres, Hanna Sofia (Universidad Antonio Nariño, 2023)
The objective of this work was to implement the use of ICT (Information and Communication Technologies) for the information management of biomedical equipment in Dr. Pava optics under authorization of the legal representative. For the development process, a research process was carried out on Colombian regulations regarding the management of biomedical technology, highlighting mainly resolution 3100 of 2019 and decree 4725 of 2005.